Hukum Melindungi Karyawan di Pabrik Kelapa Sawit Tentang Keselamatan Kerja Perspektif Imam As-Syatibi: (Studi Kasus di Desa Aek Litta Kecamatan Aek Nabara Barumun Kabupaten Padang Lawas) - Afni Saswita Siregar; Irwansyah Irwansyah; Ahmad Zuhri (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Legal protection for work safety for workers when carrying out work still involves irregularities and accidents often occur during work.. This is caused by several factors that become obstacles, especially at the palm oil factory in Aek Litta Village, Aek Nabara Barumun District, Padang Lawas Regency. The problem formulation in this research is (1) what are the work safety practices of employees at the palm oil mill in Aek Litta Village, Aek Nabara Barumun District, Padang Lawas Regency? (2) What do employees think about employee work safety at the palm oil factory in Aek Litta Village, Aek Nabara Barumun District, Padang Lawas Regency? (3) What is the legal protection for work safety in palm oil mills from Imam As-Syatibi's perspective? This research aims to determine (1) work safety practices among palm oil factory employees in Aek Litta Village, Aek Nabara Barumun District, Padang Lawas Regency. (2) employee opinions regarding the work safety of palm oil factory employees in Aek Litta Village, Aek Nabara Barumun District, Padang Lawas Regency. (3) legal protection for work safety in palm oil mills from Imam As-Syatibi's perspective. In this research the author uses an empirical juridical research method, namely examining the applicable legal provisions and what is happening in society. Then go directly into the field to see how these regulations are implemented, so that they are more detailed so that they can be analyzed and interpreted through the data collected, using sources, namely primary data and secondary data. Primary data was obtained from direct interviews with the Palm Oil Factory, namely through Mr. Sanjaya Marpaung as Manager and Mr. Alatas Siregar, Mr. Ridwan, Mr. Selamat Haidir as employees at the Palm Oil Factory. Secondary data was obtained from various literature such as books, journals related to research. . The results of the research show that (1) Work safety practices at the Palm Oil Factory, Aek Litta Village, Aek Nabara Barumun District, Padang Lawas Regency, are that the company has provided work safety personal protective equipment, there is no work safety expert available at the company and there are no pictures or posters about the use of the equipment. at the location of the palm oil processing factory (2) The employee's opinion regarding the work safety system at the Palm Oil Factory in Aek Litta Village, Aek Nabara Barumun District, Padang Lawas Regency is that the company has not been able to create a workplace that is safe and away from the risk of work accidents. There are still employees who have not complied with the regulations. (3) The legal protection for work safety in Palm Oil Factories from Imam As-Syatibi's perspective is mandatory.